SOME ASPECTS OF THE PROCESSING FLOWS FROM A STONE QUARRY - Catalina IANASI; Minodora Maria PASARE (Fiabilitate şi Durabilitate)
The stone processing and sorting installations are installations with the help of which different geometric dimensions of the processed materials are obtained. Until the final dimensions are obtained, the materials go through different stages of processing. The transfer of material, within the processing and sorting installation, is done with the help of conveyor belts. Depending on the dimensions needed to be processed, different technological routes are established so as to obtain the highest possible productivity of the process.